READER RECEPTION ANALYSIS OF THE NOVEL “BENCANA DI PLANET POA” IN "GOODREADS" CYBER LITERARY SITE - Adhitya, Novandy (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2023)
This article was created to discuss how the Reader's Reception of Djokolelono's novel Disaster on Planet Poa, whose popularity had soared when it was republished, and the rise of contemporary science fiction works in Indonesia, as well as to discuss how the acceptance of this Novel differs from function and target of its users, i.e. Goodreads literary cyber site. This research method uses qualitative descriptive research, with reception theory from Stuart Hall, which divides reader reception into three types: dominant, negotiation, and opposition. This study used content analysis techniques from data obtained from the Goodreads comment column, which was then entered into a table and reviewed with reception analysis techniques. This research found differences in readers' Reception of the Novel Disaster on Planet Poa, Where the Majority of readers chose the negotiated reception with as many as 13 readers and the dominant reception with 12 readers. In comparison, only three readers chose opposition reception.